2011
DOI: 10.2319/040311-238.1
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the midpalatal suture width

Abstract: Objective: To conduct a pilot study to investigate the potentiality to determine the midpalatal sutural width radiographically with a flat-panel volume computed tomography (fpVCT) in a porcine model. Materials and Methods: Bone samples from the midpalatal suture of five young (16 weeks) and five old (200 weeks) sus scrofa domestica were gathered. The midpalatal suture width was measured via fpVCT and compared to respective histological preparations. Results with P , .05 were considered significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 44 publications
(54 reference statements)
0
16
0
Order By: Relevance
“…In addition, these results are consistent with those reported by Reveolo et al, who showed that, although there is a significant relationship between completion of growth and initiation of ossification of the midpalatal suture, there are wide variations between the individuals in the ossification process (29). In a study by Fricke-Zech et al, it was reported that morphologic changes in suture are wide in different individuals and are not related to age only (13). In the present study, evaluation of the suture morphology did not reveal any significant differences between males and females, which is consistent with the results of a study by Revelo et al on 84 subjects (39 males and 45 females) with an age range of 8 to 18 years (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, these results are consistent with those reported by Reveolo et al, who showed that, although there is a significant relationship between completion of growth and initiation of ossification of the midpalatal suture, there are wide variations between the individuals in the ossification process (29). In a study by Fricke-Zech et al, it was reported that morphologic changes in suture are wide in different individuals and are not related to age only (13). In the present study, evaluation of the suture morphology did not reveal any significant differences between males and females, which is consistent with the results of a study by Revelo et al on 84 subjects (39 males and 45 females) with an age range of 8 to 18 years (29).…”
Section: Discussionmentioning
confidence: 99%
“…Gradually, the two halves of the maxillary bone interdigiated to some extent and cannot be separated from each other even with force and in-office appliances; the only way to separate the two halves is through surgery or surgically assisted rapid maxillary expansion (SARME) (10). Contrary to other cranial sutures, the midpalatal suture in human beings is the only suture that might not close up in the elderly (11); thus, decision to carry out SARME or RME should not be made only based on the chronological age (10, 12, 13). Although SARME is possible at any age, it is a more aggressive approach and imposes extra costs and gives rise to problems for both the patient and the orthodontist (3).…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] It is presumed that palatal halves will eventually interdigitated to that degree that even heavy forces driven by hyrax will be of no benefit, nevertheless, surgical separation of maxillary vault from midline, so called surgically assisted RPE (SARPE) is the current possible option. [ 2 ] The latter is currently performed beyond the age of 19–20, when palatal shelves could be no more separated by in-office forces and appliances. [ 2 ]…”
Section: Introductionmentioning
confidence: 99%
“…The thickness of the cortical bone was modeled according to a study by Farnsworth et al20; the thickness of the periodontal ligament was 0.2 mm21; and the width of the maxillofacial sutures was 0.5 mm 22. The mechanical properties of the cortical bone, cancellous bone, tooth, mini-plates, mini-screws, stainless steel (SS) wires, periodontal ligament, and sutures in the 3D finite element model were prepared in accordance with those described in previous investigations (Table 1).…”
Section: Methodsmentioning
confidence: 99%